Evidence gaps in conservative non-pharmacological interventions and guideline implementation for high-burden non-communicable diseases: protocol for an overview of reviews - Tobias Braun; Patrick J Owen; Daniel L Belavy; Christian Kopkow; Toni Lange; Tobias Saueressig; Rilind Shala; Jochen Zebisch; Kerstin Lüdtke; Andres Jung; Katja Ehrenbrusthoff; Rebekka Döding; et al. (BMJ Open Sport & Exercise Medicine)
Non-communicable diseases (NCDs) represent a high burden for the society and affected individuals. Conservative non-pharmacological interventions play a first-line role in the treatment and management of most NCDs. Systematic reviews (SRs) provide the highest level of evidence and significantly influence clinical decision-making. The primary aim of this study is to provide an overview of the evidence on the effectiveness of recommended conservative non-pharmacological interventions for highly burdensome NCDs. The secondary aim is to provide an overview of the evidence for guideline implementation. A literature search was performed in Medline (PubMed), EMBASE and Cochrane CENTRAL. Six reviewers will, in duplicate, independently screen and select studies following eligibility criteria. The population will include individuals with NCDs from disease categories chosen based on WHO burden of disease data and the importance of conservative rehabilitation for their management. Eligible interventions will encompass conservative non-pharmacological approaches recommended by clinical practice guidelines (ie, physical, psychological and education/advice). Eligible comparator will include no or minimal intervention and other competitive interventions. Outcomes will comprise proposed core outcomes for the respective diseases, including patient-reported (eg, pain) and performance-based (eg, physical functioning) outcomes. SRs published in the last 5 years as peer-reviewed journal article in the English language will be eligible. The overview will be reported in accordance with the Preferred Reporting Items for Overviews of reviews.